2008
DOI: 10.1104/pp.108.119339
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptomic Aspects of Urea Uptake and Assimilation in Arabidopsis Plants  

Abstract: Urea is the major nitrogen (N) form supplied as fertilizer in agriculture, but it is also an important N metabolite in plants. Urea transport and assimilation were investigated in Arabidopsis (Arabidopsis thaliana). Uptake studies using 15 N-labeled urea demonstrated the capacity of Arabidopsis to absorb urea and that the urea uptake was regulated by the initial N status of the plants. Urea uptake was stimulated by urea but was reduced by the presence of ammonium nitrate in the growth medium. N deficiency in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
99
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 56 publications
18
99
0
2
Order By: Relevance
“…12,37,38 Data reported in Arabidopsis and maize have revealed that the urea acquisition is induced by the presence in the external solution of the substrate itself. 8,39 In particular in maize roots, the high affinity transport system of urea appeared to be inducible by urea itself, retro-regulated and dependent on the external urea concentration and on the duration of root exposure to the N source. 8 Despite this physiological response to urea, transcriptional changes in plants are rather limited in this condition.…”
Section: -15mentioning
confidence: 99%
“…12,37,38 Data reported in Arabidopsis and maize have revealed that the urea acquisition is induced by the presence in the external solution of the substrate itself. 8,39 In particular in maize roots, the high affinity transport system of urea appeared to be inducible by urea itself, retro-regulated and dependent on the external urea concentration and on the duration of root exposure to the N source. 8 Despite this physiological response to urea, transcriptional changes in plants are rather limited in this condition.…”
Section: -15mentioning
confidence: 99%
“…It is possible that even though 13 C concentrations were not increased significantly in the urea treatment that the urea molecule was assimilated intact. Merigout et al (2008) showed for the plant Arabidopsis that the urea molecule was hydrolyzed in the root tissue by cytosolic ureases into two amino groups and the resulting 13 CO 2 gas would dissipate and therefore be undetectable in the root biomass.…”
Section: Don Assimilationmentioning
confidence: 99%
“…The methylerythritol phosphate pathway and farnesyl diphosphate biosynthesis lead to a reactant required for the production of chlorophyll a from chlorophyllide a (Lange and Ghassemian, 2003). In both of the GS mutant conditions, the flux through chorismate biosynthesis (Tzin and Galili, 2010), Ser biosynthesis (Ho and Saito, 2001), and the urea cycle (Mérigout et al, 2008) must decrease compared with the N + WT condition. Choline biosynthesis (McNeil et al, 2001) is decreased in the N 2 WT condition, increased in the gln1-3 mutant, and decreased in the gln1-4 mutant condition.…”
Section: Flux Range Variations Among Conditionsmentioning
confidence: 99%